1997
DOI: 10.1103/physrevlett.78.4265
|View full text |Cite
|
Sign up to set email alerts
|

Self-Interstitial Clustering in Crystalline Silicon

Abstract: We have proposed a novel model of a self-interstitial defect in crystalline Si. It contains four Si interstitials and has the structural features as follows: All silicon atoms are four coordinated, in contrast to previously proposed models; the defect is characterized by five-, six-, and seven-membered atomic rings. The total energy, the relaxed atomic configuration, and the electronic structure of the defect have been determined using the transferable semiempirical tight binding method. [S0031-9007(97)03265-1] Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
75
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(84 citation statements)
references
References 20 publications
9
75
0
Order By: Relevance
“…Further investigations are underway. The structure proposed by Takeda et al [6] for I 4 was found to be stable and its optimised structure agrees with that calculated using tight-binding methods.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Further investigations are underway. The structure proposed by Takeda et al [6] for I 4 was found to be stable and its optimised structure agrees with that calculated using tight-binding methods.…”
Section: Discussionsupporting
confidence: 75%
“…3). The energy of this structure was compared with that of a modified Takeda I 4 structure [6]. One atom was removed from this I 4 defect and the resultant structure was relaxed.…”
Section: The Neutral Tri-interstitial: Imentioning
confidence: 99%
See 1 more Smart Citation
“…Previously reported analyses of self-interstitial cluster thermodynamics generally have focused on cluster energetics at zero temperature. [4][5][6][14][15][16][17][18][19][20][21][22] These studies have employed a broad range of theory to describe interatomic interactions, ranging from empirical potentials, 4,14,15 to tight binding, [16][17][18] to electronic density-functional theory ͑DFT͒. 5,6,[20][21][22][23] While there are some discrepancies between the various studies regarding the precise values and ordering of the predicted formation energies, some general conclusions can be drawn.…”
Section: Formation Thermodynamics For Self-interstitial Clusters-prevmentioning
confidence: 99%
“…In contrast, Lopez et al did not find enough evidences to associate I 3 -I to the W line due to its high formation energy and the bad agreement of its donor level with the photon energy of the W line [15,16]. With respect to the X line, Carvalho et al suggested the tetra-interstitial Si cluster configuration proposed by Arai et al as X PL center, despite that its donor level did not agree with experimental values, and there were some discrepancies of the calculated LVMs with experiments [17]. Thus, the atomistic configurations of the W and X PL centers in c-Si remain unclear [18].…”
Section: Introductionmentioning
confidence: 97%